Sports poverty alleviation: concept and model innovation for the development of Chinese sports towns in the new Era - Liu, Sisi; Qi, Wei (Frontiers in Sports and Active Living, 2024)
In recent years, sports-themed towns have emerged as a key component in China's rural revitalization and poverty alleviation strategy, integrating sports, culture, tourism, and health industries to drive regional economic and social development. However, the literature often overlooks their long-term impact on social, cultural, and community development. Research aims to explore the concept of "sports poverty alleviation" and propose a new development model for sports towns in China, focusing on economic growth as well as social and cultural enhancement, public health, community integration.The study employs mixed methods, including documentary analysis and empirical research, to evaluate the effectiveness of various sports town models in poverty alleviation. Findings reveal that while these towns successfully boost short-term economic growth, especially through tourism and events, their sustainability is challenged by homogenization and a lack of competitiveness.Many towns fail to capitalize on local cultural and natural resources, and while they contribute to immediate economic benefits, they often lack long-term employment and integration strategies for local communities. Successful cases like the Mashan model demonstrate how integrating local resources and cultural identity with sports industries can lead to sustainable development and poverty alleviation.The research concludes that a more holistic approach to the development of sports towns in China is needed. Economic benefits should be complemented by a focus on social, cultural, and community development to ensure long-term success. The proposed innovative development models offer practical solutions to enhance the uniqueness and sustainability of sports towns, contributing to China's rural revitalization and poverty alleviation efforts.